Supernationalism. Theory of integration - Halili, Nijazi (Technium Social Sciences Journal, 2021)
In this research paper I have addressed multinational corporations, with that of non-state actors interacting with state actors. Although multinational corporations are sub-state actors in the formulation of the state's foreign policy, they are also transnational actors that transcend national boundaries and create new avenues of interdependence between states. This chapter is about transnational and international actors whose roles and influences are supranational, that is, they summarize a number within a larger whole. As we have seen, the UN has some supranational aspects, but they are limited by the UN Charter, which is based on state sovereignty. On a regional scale, the European Union (European Union, EU) is a somewhat more supernatural entity than the UN, and other regional organizations, which have achieved varying degrees of success, have tried to follow the path of Europe. The official intergovernmental organizations, the UN and the EU are not the only way to work out supranationalism. In many respects, the consequences of information technologies operating globally and regionally across state boundaries without official political structures are of longer-term impact. This chapter explores these diverse supranational influences on international politics, ranging from official EU structures to the globalizing consequences of information.